PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) DENGAN PEMBERIAN PUPUK NPK DAN HAYATI - Indah permata Sari Siagian; Balonggu Siagian; Jonatan Ginting (Universitas Sumatera Utara, 2014)
Research on title The Growth of Cacao (Theobroma cacao L.) Seedling by Using NPK Fertilizer.This research was held in resident area in Tanjung Sari from December 2012 to April 2013. Theobjective of the research was to study the effect of NPK fertilizer, biofertilizer and their interactionon cacao growth. Experiment design was arranged in group randomized design with 2 factor. Thefirst factor was rate of NPK fertilizer, consisted of 4 level: P0 (0 gram), P1(7,5 gram), P2(15gram),P3 (22,5 gram). The second factor was rate of biofertilizer, consisted 4 level : B0 (0gram), B1 (10 gram), B2 (20 gram), B3 (30 gram). Parameters observed consist of plant height(cm), the amount of leaf (sheet), stem diameter (cm), total leaf area (cm2), shoot wet weight (g),shoot dry weight (g), root wet weight and root dry weight (g).The results showed that by usingbiofertilizer affected significantly for the amount of leaf, shoot wet weight and shoot dry weight.NPK fertilizer and their interaction effect was not significant on all parameters were observed.Keywords: cacao, NPK fertilizer , biofertilizer